How Do You Watch Sports? Differences on Credibility, Viewing Satisfaction, Flow, and Re-viewing Intention between Public TV Stations and One-person Media via SNS - Chulhwan Choi; Chul-Ho Bum (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2019)
With advancements in the Internet and next-generation devices, one-person media sports broadcasts cause major changes in the sports broadcasting field, dominated by large TV broadcasting stations. The popularity of one-person media, especially among sports fans, and the presence of "influencers" with considerable impact are tremendous in the sports industry. In this context, this study assessed factors that drive media viewing based on (a) credibility, (b) viewing satisfaction, (c) flow, and (d) re-viewing intention. This study also analyzed recent sports media consumption patterns by comparing one-person media sports broadcasts with existing public TV broadcasts. The study results showed that mass appeal, flow, satisfaction with commentaries, satisfaction with video and sound, and satisfaction with the information provided significantly effect viewers' intent to re-view broadcasts in the future. Although existing TV broadcasts have more professionalism, trustworthiness, and mass appeal than one-person media, the latter provides more dynamism, satisfaction with video and sound, satisfaction with information provided, flow, and re-viewing intention. These study results indicate that rather than being a temporary trend, one-person media sports broadcasts obtained positive reactions in terms of re-viewing intention, based on high satisfaction and viewing flow of viewers, which are noteworthy in the sports media field.